2015
DOI: 10.1200/jco.2013.52.3522
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of 30-Minute Infusion of Carfilzomib As Single Agent or in Combination With Low-Dose Dexamethasone in Patients With Relapsed and/or Refractory Multiple Myeloma

Abstract: Carfilzomib administered as a 30-minute IV infusion at 56 mg/m(2) (as single agent or with low-dose dexamethasone) was generally well tolerated and highly active in patients with relapsed and/or refractory MM. These data have provided the basis for the phase III randomized, multicenter trial ENDEAVOR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 29 publications
10
86
0
Order By: Relevance
“…The toxicity profile for carfilzomib has been well established at the currently FDA-approved dose of 20 mg/27 mg 8,9 and is still being defined, but thus far is not significantly different, for doses up to 20 mg/56 mg. [23][24][25] Toxicities attributed to panobinostat in this trial are similar to those reported in other studies with this drug. 13,16,26,27 In particular there are two ongoing studies of carfilzomib/panobinostat combinations looking at alternative schedules of panobinostat compared to that used in this study.…”
Section: Grade 3 Grade 4 Totalsupporting
confidence: 80%
“…The toxicity profile for carfilzomib has been well established at the currently FDA-approved dose of 20 mg/27 mg 8,9 and is still being defined, but thus far is not significantly different, for doses up to 20 mg/56 mg. [23][24][25] Toxicities attributed to panobinostat in this trial are similar to those reported in other studies with this drug. 13,16,26,27 In particular there are two ongoing studies of carfilzomib/panobinostat combinations looking at alternative schedules of panobinostat compared to that used in this study.…”
Section: Grade 3 Grade 4 Totalsupporting
confidence: 80%
“…Carfilzomib has demonstrated anti‐tumour activity in patients with MM at doses ranging from 15 to 56 mg/m 2 (Siegel et al , 2012; Vij et al , 2012a,b; Badros et al , 2013; Papadopoulos et al , 2013, 2015). In phase I and II trials, only the LLVY‐AMC assay was used in a limited number of patient samples to measure CT‐L activity alone (O'Connor et al , 2009; Badros et al , 2013; Niesvizky et al , 2013; Papadopoulos et al , 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This has been shown to be well tolerated by reducing the incidence of infusion-related reactions. 48,49 In conclusion, the current analysis of CV events across carfilzomib clinical trials conducted to date indicates that, although cardiac AEs are numerically higher among carfilzomib-treated patients, the relative risk remains relatively low and rarely leads to dose reductions or treatment discontinuation. Moreover, the consequences are generally manageable, with no higher risk for fatal outcomes.…”
Section: Discussionmentioning
confidence: 99%